Abundance of Giant Clam in Coral Reef Ecosystem at Pari Island: a Population Comparison of 2003's to 1984's Data - Alfiani Eliata; Felicia Zahida; Wibowo Nugroho Jati; Lily M. Panggabean (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2003)
A survey on abundance of Giant Clam in coral reef ecosystem at PariIslandhas not been done long after the first survey on 1984. The survey itself is very important because Indonesian government has been release SK Menteri Kehutanan No. 12/Kpts-II/1987 and PP No. 7. th.1999 that states the giant clam is protected species. Indonesia has seven species of giant clam out of nine species presence in the world, i.e. Tridacna gigas, T.crocea, T. maxima, T. derasa, T. squamosa, Hippopus hippopus, and H. porcellanus (Rohmimohtarto dkk, 1987, Knop, 1996)